Antihyperlipidemic activity of adenosine triphosphate in rabbits fed a high-fat diet and hyperlipidemic patients. (2nd October 2016) - Zhang, Lianshan; Liang, Libin; Tong, Tong; Qin, Yuguo; Xu, Yanping; Tong, Xinglong
Abstract: Context Recently, adenosine triphosphate (ATP) was occasionally found to decrease the triglyceride (TG) levels in several hyperlipidemic patients in our clinical practice. Objective The study investigates the anti-hyperlipidemic effects of ATP in a high-fat fed rabbit model and hyperlipidemic patients. Materials and methods Twenty-four rabbits were randomly divided into three groups of eight animals each as follows: normal diet, high-fat diet and high-fat diet + ATP group. ATP supplementation (40 mg/day) was started at the 20th day and lasted for 10 days. Serum concentrations of total cholesterol (TC), TG, LDL-C, HDL-C were measured on the 20th day and 30th day. Heart, liver and aorta were subjected histopathological examination. Twenty outpatients diagnosed primary hyperlipidemia took ATP at a dose of 60 mg twice a day for 1 week. Results Feeding rabbits with a high-fat diet resulted in a significant elevation of lipid parameters including TC, TG, LDL-C, VLDL-C compared to the normal diet group ( p < 0.01). ATP treatment significantly decreased serum TG level ( p < 0.01), whilst other parameters remained statistically unaltered. Meanwhile, ATP significantly reduced the thickness of fat layer in cardiac epicardium ( p < 0.05) and pathological gradation of ballooning degeneration in hepatocytes ( p < 0.05). After taking ATP for 1 week, hyperlipidemia patients exhibited a significant decrease of TG ( p < 0.01), but other lipid parameters had no significant change. Discussion and conclusion The study indicates that ATP selectively decreases serum TG levels in high-fat diet rabbits and hyperlipidemic patients. Therefore, ATP supplementation may provide an effective approach to control TG level.